2003
DOI: 10.1055/s-2003-37959
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Neuralgia Presenting as Chiari I Malformation

Abstract: Chiari I malformation usually presents with headache, numbness, weakness and gait abnormalities. We present a 38-year-old female with trigeminal neuralgia who was found to have a Chiari I malformation. She had a foramen magnum decompression with complete resolution of her symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…investigate the singlet eigenstates using variational exact diagonalization (VED) [31][32][33] and an extension of the Momentum Average (MA) approach [22,30,[34][35][36].…”
mentioning
confidence: 99%
“…investigate the singlet eigenstates using variational exact diagonalization (VED) [31][32][33] and an extension of the Momentum Average (MA) approach [22,30,[34][35][36].…”
mentioning
confidence: 99%
“…[4][5][6]14,17 In cases in which hydrocephalus was present along with the CM, cerebrospinal fluid diversion through a ventriculoperitoneal shunt 8 or via endoscopic third ventriculostomy 16 was sufficient. Our patient regained her facial sensation and gag reflex following posterior fossa decompression and partial C-1 laminectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellopontine angle schwannomas and other tumors, multiple sclerosis and Chiari malformation have been previously reported. [2][3][4]7 Trigeminal neuralgia with Dandy-Walker malformation, as reported here, may be coincidental; however, there may be an etiological association between Dandy-Walker malformation and trigeminal neuralgia. We suggest that trigeminal neuralgia associated with a Dandy-Walker cyst may be caused by traction and direct deformation of the nerve, rather than vascular compression as is usually thought to be the case.…”
Section: Introductionmentioning
confidence: 86%
“…1 Imaging studies have demonstrated an increased incidence of intracranial arachnoid cysts in patients with ADPKD. 2 Chronic subdural haematoma (CSDH) as a complication of arachnoid cyst is well documented 3-6 but its association with arachnoid cyst in ADPKD has not been reported. [7][8] We report a case of CSDH complicating an intracranial arachnoid cyst in a patient with ADPKD.…”
Section: Introductionmentioning
confidence: 99%